2015
DOI: 10.1002/lt.24038
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic status in liver transplantation: Association between preoperative procoagulants/anticoagulants and postoperative hemorrhaging/thrombosis

Abstract: The delicate rebalanced hemostatic status of liver transplant recipients may lead to both hemorrhagic and thrombotic tendencies in this population. The aim of this study was to investigate the association between pretransplant procoagulants/ anticoagulants and posttransplant bleeding and thrombosis among living donor liver transplant recipients. The study subjects were 403 consecutive recipients with chronic liver disease. Perioperative variables, including preoperative values for procoagulants and anticoagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…(18) Our posttransplant anticoagulation regimen was also described previously. (19) sHUnt evalUatiOn A shunt was defined as a natural venous communication between portal and caval systems in the presence of liver cirrhosis. A pre-LDLT 3-dimensional, enhanced computed tomography scan at the venous phase (within 1 month prior to LT) was reviewed by an author (M.A.A.)…”
Section: Original Article | 79mentioning
confidence: 99%
“…(18) Our posttransplant anticoagulation regimen was also described previously. (19) sHUnt evalUatiOn A shunt was defined as a natural venous communication between portal and caval systems in the presence of liver cirrhosis. A pre-LDLT 3-dimensional, enhanced computed tomography scan at the venous phase (within 1 month prior to LT) was reviewed by an author (M.A.A.)…”
Section: Original Article | 79mentioning
confidence: 99%
“…The plasma concentration of coagulant and anticoagulant proteins is disturbed after liver transplantation, leading to a hypercoagulable condition that contributes to vascular thrombosis with an incidence rate of 5%. 19 In our cases, however, the anticoagulation protocol involving xueshuantong injection, aspirin, and Gingko leaves extract was effective to prevent formation of thrombosis in the hepatic portal system and splenic vein.…”
Section: Discussionmentioning
confidence: 53%
“…Abdominal bleeding is related to the preoperative patients' condition, operation techniques and postoperative anticoagulation 34,35 . Nobuhisa et al 36 reported that a higher MELD score, intraoperative blood loss and low brinogen value increase the incidence of postoperative abdominal bleeding. Our result revealed that it was not signi cantly different among the different techniques.…”
Section: Discussionmentioning
confidence: 99%